Key genes of vitamin D metabolism and their roles in the risk and prognosis of cancer - Zheng, Sijie; Zhu, Lizhu; Wang, Yufei; Hua, Yixin; Ying, Jie; Chen, Jianxiang (Frontiers in Genetics, 2025)
Vitamin D is an essential vitamin for normal human metabolism and plays pivotal roles in various biological processes, such as maintaining calcium and phosphorus balance, regulating immune responses, and promoting cell differentiation while inhibiting proliferation. Vitamin D is obtained through sunlight exposure and diet, and is metabolized into its active form via hydroxylation in liver and kidney. Vitamin D deficiency is linked to various diseases, including skeletal disorders, diabetes, and cardiovascular diseases. Recent epidemiology and oncology research have demonstrated that serum vitamin D level, as well as genetic polymorphisms and expression dysregulation of genes related with vitamin D metabolism, have significantly influences on the incidence and prognosis of various types of cancer, including breast cancer, prostate cancer, liver cancer, gastrointestinal malignancy, and hematologic malignancies. The mechanisms linking vitamin D metabolism dysregulation to malignancy are multifactorial, such as the alteration in cell metabolism, proliferation, differentiation, and tumor microenvironment. These findings suggest potential therapeutic benefits of targeting the vitamin D signaling pathway for the diagnosis and treatment of cancer. However, there is still a lack of clinical applications regarding the knowledge of vitamin D metabolic pathway, and future research is urgently needed to illustrate the underlying mechanisms for the rationale design of clinical trials. Therefore, this review summarizes the metabolic pathways of vitamin D and its association with cancer, highlighting the importance of genetic polymorphisms and expression dysregulation of genes involved in vitamin D metabolism in cancer susceptibility and prognosis.